The impact of Online Customer Review, Content Marketing, and Live Streaming on Purchase Decisions on Shopee with Trust as Mediation - Abidin, Alia; Janfry Sihite (Indonesian Journal of Business Analytics, 2024)
The study aims to analyze the impact of Online Customer Review, Content Marketing, and Live Streaming on Purchase Decisions on Shopee with Trust as Mediation. The population in this study is Generation Z (born 1997-2012) who are based in Jakarta and have been shopping at Shopee at least 1 time or more, with the sample number obtained as many as 176 respondents. The results of this study show that Online Customer Review and Content Marketing have a positive and significant influence on Purchase Decisions, but Live Streaming has a negative and significant impact on Purchasing Decision. Trust is unable to mediate the influence between Online Customer Review and Live Streaming with Purchase Decisions, but Trust is capable of mediating influences between Content Marketing as a partial mediation with Purchasing Decision.